UNIVERSITY AUTONOMY IN THE REGULATORY AND LEGAL ACTS OF EASTERN EUROPEAN COUNTRIES - Oksana Bulvinska (Неперервна професійна освіта: теорія та практика)
The article is dedicated to analyzing regulatory and legal acts in Eastern European countries concerning university autonomy and academic freedom, which are often intertwined in legal documents. The study examines documents from Eastern European countries – Poland, Hungary, Romania, Slovakia, and the Czech Republic – which are geographically, historically, and culturally close to Ukraine and share a common totalitarian past. The analysis focuses on Constitutions as well as national Higher Education Laws. It is emphasized that enshrining university autonomy in the fundamental laws of a country does not automatically imply a high level of its actual development; however, it elevates it to the status of a fundamental value. The research findings indicate that only the Constitutions of two countries – Poland and Romania – contain precise wording on university autonomy. The national Higher Education Laws in all the analyzed countries, oriented toward the Europeanization of education and university autonomy as a core value and governance principle of the European Higher Education Area, fully regulate the distribution of powers between the state and universities in organizational, financial, personnel, and academic activities. Hungary represents a separate case, as its legislation formally restricts university autonomy in favor of state regulation of higher education, which has drawn criticism from both scholars and executive bodies of the European Union.